PENGARUH PEMEREKAN KOTA “ENJOY JAKARTA” TERHADAP CITRA KOTA - Chandra Wibowo Widhianto; Henilia Yulita (Journal of Business & Applied Management, 2016)
Jakarta, as the capital of the Republic of Indonesia, finally for the first time launched the "EnjoyJakarta" on March 21, 2005. The main reason for the launched program is to increase the number offoreign tourists as many as 2.2 million visitors or twice as compared to year 2014. This studyexamines the effect of Jakarta‟s city brand: “Enjoy Jakarta” to city image. Data were obtained from110 respondents who are citizens of Jakarta and outside Jakarta. This type of research is associativeresearch conducted to link the variable with other variables. The results showed that the ANOVA (Ftest) simultaneously variables city brand has a significant effect on the image of the city indicatedvariables of the Sig. 0,000 <Alpha 5%. Variables city brands accounted for 51.9% of the variableschange the image of the city, while the remaining 48.1% is explained by other variables outside themodel.Keywords: City Brand, City Image